Analysis of Alkali-Induced Soil Heaving in Non-Expansive Soil Using Electrokinetic Model - Mandal, Manish Kumar; Paramkusam, Bala Ramudu (Technoscience Publications, 2022)
An attempt has been made in this paper to conduct an Electrokinetic (EK) enhanced large-scale model study to analyze the heaving phenomena observed in fields. The application of the EK technique on fields to study alkali-induced heaving has been simulated in the laboratory using a rectangular and circular model. The EK technique was mainly employed to facilitate alkali soil interaction. Analysis of the geometry of the model boundary on the various physiochemical as well as geotechnical properties of the soil was conducted. Before that, a simple heaving analysis was also performed in an oedometer without the EK technique. Compare to the maximum heaving of 5.55% observed in the oedometer the soil in EK-equipped circular and rectangular models showed the heaving of 5.42% and 4.21% respectively. The heaving pressure recorded for the oedometer was 67.5 t.m-2 while for the circular and rectangular models these values were 37.7 t.m-2 and 18.8 t.m-2 respectively. Further, the value of unconfined compressive strength of soil decreases from 141 kPa to 80 kPa after interaction with alkali and the decrease was more prominent in the circular EK model. However, there was an increase in the friction angle and a decrease in cohesion value after alkali interaction. The structural alteration due to alkali solution was examined by SEM and XRD analysis.
This paper is submitted by the author of IIT(BHU),Varansi
Keywords: alkalinity; compressive strength; electrokinesis; friction; geotechnical property; induced response; numerical model; soil analysis